Feasibilty of Transcutaneous pCO2 Monitoring During Immediate Transition After Birth—A Prospective Observational Study - Bresesti, Ilia; Bruckner, Marlies; Mattersberger, Christian; Baik-Schneditz, Nariae; Schwaberger, Bernhard; Mileder, Lukas; Avian, Alexander; Urlesberger, Berndt; Pichler, Gerhard (Frontiers in Pediatrics, 2020)
BACKGROUND: According to recommendations, non-invasive monitoring during neonatal resuscitation after birth includes heart rate (HR) and oxygen saturation (SpO2). Continuous transcutaneous monitoring of carbon dioxide partial pressure (tcpCO2) may further offer quantitative information on neonatal respiratory status. OBJECTIVE: We aimed to investigate feasibility of tcpCO2 measurements in the delivery room during immediate neonatal transition and to compare the course of tcpCO2 between stable term and preterm infants. METHODS: Neonates without need for cardio-respiratory intervention during immediate transition after birth were enrolled in a prospective observational study. In these term and preterm neonates, we measured HR and SpO2 by pulse oximetry on the right wrist and tcpCO2 with the sensor applied on the left hemithorax during the first 15 minutes after birth. Courses of tcpCO2 were analyzed in term and preterm neonates and groups were compared. RESULTS: Fifty-three term (gestational age: 38.8±0.9 weeks) and 13 preterm neonates (gestational age: 34.1±1.5 weeks) were included. First tcpCO2 values were achieved in both groups in minute 4 after birth, which reached a stable plateau after the equilibration phase in minute 9. Mean tcpCO2 values 15 minutes after birth were 46.2 (95% CI 34.5-57.8) mmHg in term neonates and 48.5 (95%CI 43.0-54.1) mmHg in preterm neonates. Preterm and term infants did not show significant differences in the tcpCO2 values at any time point. CONCLUSION: This study demonstrates that tcpCO2 measurement is feasible during immediate neonatal transition after birth and that tcpCO2 values were comparable in stable term and preterm neonates.